Living bioethics, clinical ethics committees and children's consent to heart surgery. (September 2022) - Alderson, Priscilla; Bowman, Deborah; Brierley, Joe; J. Elliott, Martin; Kazmi, Romana; Mendizabal-Espinosa, Rosa; Montgomery, Jonathan; Sutcliffe, Katy; Wellesley, Hugo
This discussion paper considers how seldom recognised theories influence clinical ethics committees. A companion paper examined four major theories in social science: positivism, interpretivism, critical theory and functionalism, which can encourage legalistic ethics theories or practical living bioethics, which aims for theory–practice congruence. This paper develops the legalistic or living bioethics themes by relating the four theories to clinical ethics committee members' reported aims and practices and approaches towards efficiency, power, intimidation, justice, equality and children's interests and rights. Different approaches to framing ethical questions are also considered. Being aware of the four theories' influence can help when seeking to understand and possibly change clinical ethics committee routines. The paper is not a research report but is informed by a recent study in two London paediatric cardiac units. Forty-five practitioners and related experts were interviewed, including eight members of ethics committees, about the work of informing, preparing and supporting families during the extended process of consent to children's elective heart surgery. The mosaic of multidisciplinary teamwork is reported in a series of papers about each profession, including this one on bioethics and law and clinical ethics committees' influence on clinical practice. The qualitative social research was funded by the British Heart Foundation, in order that more may be known about the perioperative views and needs of all concerned. Questions included how disputes can be avoided, how high ethical standards and respectful cooperation between staff and families can be encouraged, and how minors' consent or refusal may be respected, with the support of clinical ethics committees.